HAK VETO DEWAN KEAMANAN PERSERIKATAN BANGSA-BANGSA DAN ASAS EQUALITY OF THE STATES DALAM ERA GLOBALISASI - Adventura, Battista Pridana (Justitia et Pax, 2021)
The Security Council is one of the organs of the United Nations to assist its task in maintaining world security and peace. In carrying out its duties, the Security Council is guided by the principles known in the United Nations, as regulated in Article 2 paragraph 1 of the United Nations Charter. One of the principles is the equality of position or degrees of all member countries. But the phenomenon that occurs is the opposite, equality of position is not respected in the UN Security Council considering that in making decisions, it is known that there is a veto that only applies owned by a permanent member state of the Security Council and this right is often used to carry out foreign policy and maintain interests with allied countries. Seeing this phenomenon, is the veto power still relevant today? And are there any attempts to reduce or limit the permanent member states of the UN Security Council from exercising that veto? The purpose of this study is to identify whether or not there is a need for reform of the use of the veto power which incidentally is not by the principle of equity of the states. This research uses normative legal research. The conclusion of this paper is every country has the same position, but the current phenomenon is a country that has strong power, will affect other countries, as evidenced by the three cases discussed in this paper, then the veto right shows the privilege for the five founders of the United Nations compared to other countries.